Integrative approach to obesity management: Ayurvedic & Modern perspective - Singh, Shoban; Tiwari, Mamta; Nathani, Professor Neeru (International Research Journal of Ayurveda & Yoga, 2026)
Modernization , affluence , and advancements in science and technology have led to increase in sedantary lifestyle which unintentionally invites a range of health issues one of which is Sthaulya (Obesity). Sthaulya affects physical ,mental, and social health. Sthaulya (Obesity) is considered a principal public health concern and ranked as the fifth foremost reason for death globally. Overweight and obesity are one of the main lifestyle disorder that leads to further health concerns and contributes to numerous chronic disease including cancers, diabetes , metabolic syndrome and osteoarthritis , cardiovascular disease. Ayurvedic management of obesity adopts a comprehensive and individualized approach aimed at restoring doshic balance, enhancing metabolic function, and reducing excess adiposity. Therapeutic strategies include dietary regulation (Ahara), lifestyle modifications (Vihara), pharmacological interventions using herbal formulations, and bio-purificatory therapies (Panchakarma). According to Ayurveda Sthaulya (obesity) is caused due to over-nourishment as a consequence of the intake of a heavy, Obesity is a complex, multifactorial condition influenced by genetics, environment, behavior and lifestyle .With the rapid pace of industrialization and economic progress, more occupations are becoming sedentary and dietary patterns are also changing with a decline in healthy diet intake and increase in intake of unhealthy food i.e sugar,fats, processed food . India is in 7th place in terms of obesity index. Lifestyle changes are considered the cornerstone in both prevention and management of Sthaulya (obesity). These changes target the root causes, such as poor diet, physical inactivity, poor sleep and chronic stress. Sthaulya (obesity) is not merely a matter of excess weight,it is associated with a wide range of metabolic and systemic complications including Type 2 Diabetes, Hypertension, cardiovascular diseases, and certain cancers. These comorbidities significantly contribute to increased morbidity and mortality worldwide.